Good Practices in Transfer Education Report from a Survey Conducted by the American Association of Community and Junior Colleges and the National Center for Academic Achievement and Transfer. Transfer Working Papers, Volume 1, Number 3, October 1990. - American Association of Community and Junior Colleges; American Council on Education. National Center for Academic Achievement and Transfer ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
In April 1990, the American Association of Community and Junior Colleges and the National Center for Academic Achievement and Transfer conducted a national survey of 1,366 regionally accredited, degree-granting, two-year public and private colleges to identify practices used to foster and encourage student transfer to senior institutions. Institutions were asked to describe the frequency with which they employed various transfer strategies, their method of identifying transfer students, and their approach to calculating institutional transfer statistics. Study findings, based on a 39.4% response rate, included the following: (1) the institutions utilized written articulation agreements (85%), course equivalency guides (81%), and transfer counselors (81%); (2) additional transfer strategies employed included joint degree programs, dual registration, transfer information centers, intercollegiate relations commissions, and guaranteed admissions to receiving institutions; (3) the most popular methods used to identify students who transferred were graduate follow-up surveys, estimates/guesses, state reporting systems, documentation of transcript requests, and information obtained from senior institutions; and (4) most institutions based transfer statistics on recent associate degree graduates or students enrolled in transfer curricula, producing higher transfer rates than institutions considering the entire student population in estimating transfer rates. Recommendations for future research are included. (GFW)
Sponsoring Agency: Ford Foundation, New York, NY.
Transfer Working Papers, v1 n3 Oct 1990.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Articulation (Education); College Transfer Students; Community Colleges; Data Collection; Higher Education; National Surveys; Research Methodology; Transfer Policy; Transfer Programs; Transfer Rates (College); Two Year College Students; Two Year Colleges; Reports, Research